FORMULASI LARUTAN DETERGEN DARI NATRIUM DODESIL SULFAT DAN SINTESIS NATRIUM DODESILBENZENA SULFONAT - Adi N, Wiedy Paristya (Chem Info Journal, 2013)
Detergent products has been used by almost all the inhabitants for various purposes such as washing clothes and furniture as well as other cleaning materials. Surfactants are good for cleaning are anionic surfactants, ionic surfactants in water kelaruan optimal C12 chain. Some anionic surfactant C12 made and developed, one of which was sodium dodecyl sulfate (SDS). Synthesis of sodium sulfonate dodesilbenzena was performed to compare dodesilbenzena detergency sodium sulfonate synthesized with sodium dodecyl sulfate. The ability of surfactants to removing contaminants less than perfect so necessary to the addition of sodium tripolyphosphate (STPP) as a builder, carboxymethyl cellulose (CMC) as well as the alkaline pH and buffer needs to be added besides the addition of STPP. Detergency sodium dodecyl sulfate (SDS) with the optimum addition of STPP 60%, pH 10.5; CMC 1%. Formula detergent was surfactant SDS obtained 23%; STPP 60%; CMC 1%; buffer NaHCO3 - NaOH and Na 2SO4 with a detergency of 86.989%. GC-MS analysis of the results of alkylating Friedel craft (phase 1), the spectra showed that the compound formed is Dodesilbenzene with tR 18.84, SI = 96. The results of neutralization (phase 3) has a melting point> 500oC estimated inorganic compounds.